Matricial inclusion of AlN and Al2O3 nanoparticles in C/C composites from aqueous growth and ceramization at the pre-densified stage. Issue 18 (15th December 2017) - Martin, Nicolas; Plaisantin, Hervé; Weisbecker, Patrick; Leyssale, Jean-Marc; Pailler, René
Abstract: We report on a successful attempt to introduce Al 2 O 3 and AlN nanoparticles in the matrix of a C/C composite via (i) aqueous synthesis of AlOOH nanoparticles in a predensified C/C composite preform, (ii) ceramization of AlOOH into either Al 2 O 3 or AlN, and (iii) final pyrocarbon densification. We show that we were able to synthesize a uniform and thin layer of high aspect ratio (nanoneedle) AlOOH particles at the surface of pyrocarbon coated fibers. This morphology was conserved upon transformation to alumina, however, coalescence into larger compact grains (thus discontinuous) was observed after nitridation. Nevertheless, the ceramic introduction did not alter the microstructure of the resulting composite after full densification. While most of the ceramic/carbon interfaces showed a parallel arrangement of graphene layers at the surface of the ceramic particles, characteristic of weak bonding, a carbon/AlN interface showed a perpendicular arrangement, suggesting strong covalent bonding.